Easy statistics: quick stats fundamentals: a beginner's guide - Bahrom, Suhaila; Abu Hassan, Fatin Zahida (Self-Published, 2024)
This e-book is designed to introduce beginners to the fundamentals of statistics in an accessible and straightforward manner. It covers essential statistical concepts such as sampling methods, frequency distribution, measures of central tendency, variability, position, and types of distribution. This e-book is likely structured to provide clear explanations to help readers grasp these concepts easily. It aims to demystify statistics and empower beginners to understand and apply statistical techniques confidently.